Infarcted accessory spleen masquerading as a mesenteric cyst. (16th August 2018) - Sheth, Harsh; Chaudhari, Sadashiv; Sinha, Yash; Prajapati, Ramlal
Abstract : An accessory spleen is a rare entity which is usually asymptomatic. When symptomatic, it presents as an acute abdomen, with either torsion, rupture or haemorrhage. We present the case of a 20-year-old man who presented with chronic lower abdominal pain since 3 months and a lump in the left lower quadrant. On clinical examination and investigations, the lump was diagnosed as a mesenteric cyst, and an uncomplicated laparoscopic excision was performed. The postoperative histopathological examination reported it as an infarcted accessory spleen.